Topical nanomedicines for leishmaniasis and skin cancer based on photodynamic and photothermal therapies - Maza Vega, Daniela; Lillo, Cristian R.; Aguayo Frías, Eliana Taís; Astorga, Laura; Lemos Vilches, Martín; Alonso, Silvia del Valle; Calienni, María Natalia; Alvira, Fernando Carlos; Montanari, Jorge (Atatürk University. Nanotechnology Application and Research Center (ITU Nano), 2021)
Tegumentary leishmaniasis and skin cancer are skin diseases that require new approaches for the improvement of current treatments. Our group focuses on combining lipid matrices for trespassing the stratum corneum impermeable barrier, with photochemistry-based therapies for toxicity or hyperthermia to kill cells in a very narrow area.For leishmaniasis, intending to reach the parasite nests into skin macrophages, we work on one hand with carbon quantum dots (CQD), obtained from the most popular infusion in Argentina, named yerba mate (Ilex paraguariensis), and from the most popular infusion in Turkey, named çay (Camellia sinensis). CQD are produced from the vegetable residues from infusion by a top-down method (1). We analyzed their fluorescence and absorbance spectra, for choosing the best excitation and emission windows to generate a photodynamic effect, in which reactive oxygen species (superoxide anion and singlet oxygen) that are toxic for parasites, are produced after exposure to visible radiation. We show our results on the detection of both species. Other physicochemical characterization parameters of our CQD (size by dynamic light scattering, TEM, Zeta potential) are also presented. We include the CQD on ultradeformable ethosomes, that transiently break the barrier function of the stratum corneum, allowing the photodynamic effectors to enter the skin towards the viable epidermis and dermis. We use fluorescent labels to follow the ethosomes on their path through the skin (2). On the other hand, another strategy intended for leishmaniasis treatment is the use of ultradeformable ethosomes as a transport system for the dye methylene blue (3), also for generating reactive species of oxygen after irradiation with visible light. In both strategies, we plan to test the photodynamic action in vitro on leishmania parasite cultures.For skin cancer, we started working on other kinds of CQD, also from vegetable sources ?i.e., fruit juices (4)?, aiming to produce an increment of local temperature after irradiation to a level that diminishes cell viability, which is known as photothermal therapy. In this case, after obtaining the CQD, a folate moiety is added to the nano-entities for specific tumor targeting (5), and then also loaded into ultradeformable ethosomes for skin application.
Keywords: Ciencias médicas y de la salud::Biotecnología médica::Biotecnología relacionada con la salud